2007
DOI: 10.1002/pola.22379
|View full text |Cite
|
Sign up to set email alerts
|

Functionally terminated poly(methyl acrylate) by SET‐LRP initiated with CHBr3 and CHI3

Abstract: The single‐electron transfer living radical polymerization (SET‐LRP) of methyl acrylate initiated with bromoform (CHBr3) and iodoform (CHI3) and catalyzed by Cu(0)/Me6‐TREN in DMSO at 25 °C provides a reliable method to prepare poly (methyl acrylate) (PMA) with active chain ends and controlled structure that can undergo subsequent functionalization to provide strategies for the synthesis of different block copolymers and other complex architectures. A detailed kinetic and structural analysis was used to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
91
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 28 publications
2
91
0
Order By: Relevance
“…Since its discovery single electron transfer living radical polymerization (SET‐LRP)1–4 has received great attention for its highly robust and tolerant nature,5, 6 including compatibility with commercially available stabilized monomers,7 monomers containing carboxylic acid groups such as methacrylic acid,8, 9 and monomers containing OH groups such as carbohydrates 10, 11. Most importantly, SET‐LRP allows for ultrafast polymerization at ambient temperature with excellent control over the molecular weight evolution and distribution, and perfect or near perfect retention of chain end funtionality 1, 3, 12–14. SET‐LRP is remarkably effective for a wide variety of important monomers such as functional acrylates,15 acrylamides,16, 17 methacrylates,8, 18–22 methacrylic acid,9 and acrylonitrile 23, 24.…”
Section: Introductionmentioning
confidence: 99%
“…Since its discovery single electron transfer living radical polymerization (SET‐LRP)1–4 has received great attention for its highly robust and tolerant nature,5, 6 including compatibility with commercially available stabilized monomers,7 monomers containing carboxylic acid groups such as methacrylic acid,8, 9 and monomers containing OH groups such as carbohydrates 10, 11. Most importantly, SET‐LRP allows for ultrafast polymerization at ambient temperature with excellent control over the molecular weight evolution and distribution, and perfect or near perfect retention of chain end funtionality 1, 3, 12–14. SET‐LRP is remarkably effective for a wide variety of important monomers such as functional acrylates,15 acrylamides,16, 17 methacrylates,8, 18–22 methacrylic acid,9 and acrylonitrile 23, 24.…”
Section: Introductionmentioning
confidence: 99%
“…So far, only multiblocks consisting of acrylates have been reported by copper-mediated living radical polymerization and although the dispersity values were narrow in most cases, extremely long reaction times (up to 48 h per block) proved to be a limitation (24,72,73). However, the authors utilized three commercially available acrylamide monomers and managed to synthesize a well-defined hexablock copolymer P(NIPAM) 10 Subsequently, Haddleton et.al were interested in studying the effect of the structure of the monomer in these chain extensions. A detailed study revealed that NIPAM was less susceptible to termination (mainly defined as hydrolysis) in comparison with HEAA, which was capable of more chain extensions than DMA or N,N-diethyl acrylamide (DEA) (71).…”
Section: Figure 5 Schematic Representation and Sec Of A Heptablock Cmentioning
confidence: 94%
“…Alkyl halide initiators and N-containing aliphatic ligands, previously employed by atom transfer living radical polymerization (ATRP) (4-7) are utilized for the polymerization while Cu(0) (in the form of powder (8)(9)(10)(11) or wire (12)) is the proposed activator. Currently there is a debate in the literature (13,14) regarding the mechanism of CRP in the presence of Cu(0), however, this will not be the focus of this current contribution.…”
mentioning
confidence: 99%
“…As the outer sphere SET process has low activation energy, the P‐X bond dissociation energy is very low, which is heterolytically dissociated in a step‐wise or concerted mechanism mediated by an outer sphere. This means that SET‐LRP provides access to a broader range of initiators, monomers, catalysts, and synthesis for the synthesis of macromolecules with complex architecture 33–35. For example, SET‐LRP is remarkably effective for a wide variety of important monomers such as functional acrylates,4,22,36 acrylamides,37,38 methacrylates,25,27,39–45 methacrylic acid,46,47 vinyl chloride,4,6,22,48,49 and acrylonitrile (AN) 50…”
Section: Introductionmentioning
confidence: 99%